The Assessment of the Mathematics Book for the Second Basic Grade According to the Teachers in Tulkarm District Point View - Herzallah, Husam Tawfeeq (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to assess the mathematics book for the second basic grade in the governmental schools of Tulkarm District, for the first semester of the scholastic year 2018\2019; it also aimed to identify the statistically significant differences between the responses of the study sample's items according to the gender, years of experience, the scientific qualification, and the specialization variables. For the sake of data collection, the researcher designed a questionnaire as the tool of the study. the sample was stratified according to the gender variable and consisted of (40) teachers, male and female, of the governmental schools in Tulkarm District, which equaled (36%) from the original society of the study. The findings of the study have shown that the assessment of the mathematics book for the second basic grade was high on the total score of the output and the general format, while it was mediate for the content and evaluation axes; the findings also have indicated no differences in the assessment's mean from the teachers point view according to the teacher's gender, years of experience, the scientific qualification, and the specialization.On the light of the findings, some recommendations were stated, and among them are: Refining the book's content and being aware of the individual differences between students, and fitting the book to the students in the second grade, in addition to the amendment of some scientific mistakes in the book, though they are few, so as to make it at its best to be taught to the students in that level, finally, the study recommended performing a similar study for assessing the mathematics book for the second basic grade but for the second semester.
Keywords: assessment; mathematics book; second grade